DIGITAL COMMERCE BERBASIS REHABILITASI BERSUMBERDAYA MASYARAKAT BAGI DIFABEL SLB KEMALA BHAYANGKARI GRESIK - Abdurrahman Faris Indriya Himawan; Riska Widiyanita Batubara (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2022)
The increasingly advanced technology gives rise to many new media that allow the development of marketing communications such as interactive television, the Internet, E-commerce, interactive telephone, and faxing. This led to changes in market segmentation, as well as the way to communicate with them. Then the cultural driving factor makes marketing communication more segmented but its reach is very broad. Certain cultures will receive communication that is appropriate to their culture. Each tool in the promotion mix has different characteristics and it is undeniable that there are still many companies that rely on one or two promotional tools to achieve their communication goals. This is in line with the marketing communication paradigm in the past which often used advertising as the